GNSS performance modelling for high interrity aircraft applications - Shao, Liang (Cranfield University, 2012)
Till recently, no significant attempts have been made of developing Aircraft Based Augmentation System (ABAS) architectures capable of generating integrity signals suitable for safety-critical GNSS applications and no commercial ABAS products are available at present. The aim of this research is to support the design a system that generates integrity signals suitable for GNSS application. The conceptual design and key mathematical models were recently developed by the Italian Air Force Experimental Flight Test Centre (CSV-RSV) [1, 2]. Such a system, would be able to provide steering information to the pilot, allowing for real-time and continuous integrity monitoring, avoidance of safety/mission-critical flight conditions and fast recovery of the required navigation performance in case of GNSS data losses. The key elements addressed in this thesis are the development of a CATIA model for military and civil aircraft, supporting antenna obscuration and multipath analysis. This is to allow the ABAS system to generate suitable integrity flags when satellites signals are lost. In order to analyse the GNSS signal loss causes, the GNSS constellation models, the flight dynamics models, fading models, multipath models, Doppler shift models, and GNSS receiver tracking technology previously developed by CSV-RSV, are considered in this research.
Keywords: GNSS; Integrity Flag; Obscuration; Doppler Shift; Multipath; Fading; Receiver Tracking